Hypochondriacal development via expansive paranoia-type in patients with reproductive organ malignancies - S. V. Ivanov; M. A. Samushia; V. V. Kuznetsov; V. A. Gorbunova; V. P. Kozachenko; V. V. Barinov; E. A. Mustafina (Опухоли женской репродуктивной системы, 2014)
The paper characterizes paranoic hypochondriacal development, that is comparable with expan-sive paranoia, in patients with a >5-year history of malignancies at examination. A study sample comprised 8 treated out- and inpatients (mean age 55.7±7.02 years) diagnosed as having repro-ductive organ malignancies. Their examination was made by the clinical catamnestic technique. Psychopathological disorders in the described cases of expansive paranoia are associated with the development of abnormal querulant activity that is aimed at having the medical care volume inadequate to the somatic status of patients with malignancies.The described variant of development of paranoid disorders enables their determination within the framework of cancer-induced chang- es in personality disorders with the formation and further reinforcement of the psychopathological manifestations of mainly the hy- poparanoia type. The constitutional predictors of hypochondriacal development via expansive paranoia type, which include not only certain types of personality disorders (paranoic, 50%; schizoid–expansive pole, 12.5%; icteric, 37.5%; sensitive, 12.5%), but also ac- centuations (segmental depersonalization accentuation) against which the study reactions manifest themselves as a continuation of but ab-normally transformed constitutional properties.